European Black Elderberry Fruit Extract Inhibits Replication of SARS-CoV-2 In Vitro - Setz, Christian; Fröba, Maria; Große, Maximilian; Rauch, Pia; Auth, Janina; Steinkasserer, Alexander; Plattner, Stephan; Schubert, Ulrich (Nutraceuticals, 2023)
Coronavirus disease-19 (COVID-19) is still affecting the lives of people round the globe and remains a major public health threat. The emergence of new variants more efficiently transmitted, more virulent and more capable of escaping naturally acquired and vaccine-induced immunity creates a long-term negative outlook for the management of the pandemic. The development of effective and viable prevention and treatment options to reduce viral transmission is of the utmost importance. The fruits of the European black elderberry and extracts thereof have been traditionally used to treat viral infections such as coughs, cold and flu. Specifically, its efficacy against the Influenza A virus has been shown in vitro as well as in human clinical trials. In the current project, we investigated the antiviral activity of a black elderberry extract, mainly containing anthocyanins and phenolic compounds, against SARS-CoV-2 and its variants of concern and explored the possible mode of action by performing time of addition experiments. The results revealed that the extract displayed a strong anti-SARS-CoV-2 activity against the Wuhan type as well as the variants of concern Alpha, Beta, Gamma, Delta and Omicron with a comparable antiviral activity. Based on cytotoxicity data, a 2-log theoretical therapeutic window was established. The data accumulated so far suggest that the viral replication cycle is inhibited at later stages, inasmuch as the replication process was affected after virus entry. Therefore, it would be legitimate to assume that black elderberry extract might have the potential to be an effective treatment option for SARS-CoV-2 infections.
CRIS-Team Scopus Importer:2025-07-10
Keywords: anthocyanins; antiviral; coronavirus; COVID-19; European black elderberry extract; natural substance; phenolic compounds; SARS-CoV-2; SARS-CoV-2 variants of concern